Pengaruh Good Corporate Governance, Struktur Modal,dan Kinerja Keuangan terhadap Harga Saham Perusahaan Sektor Financials - Rosita Diyah Ramadhani; Sigit Puji Winarko; Erna Puspita (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
The capital market is crucial for fostering a nation's economic growth, serving as both a financing source for enterprises and an investment avenue for the public. Stock prices serve as a vital sign of investors' thoughts about a company's future potential. Stock price volatility is significantly affected by several variables, including Good Corporate Governance (GCG), capital structure, and financial performance. This research seeks to examine the impact of Good Corporate Governance (GCG), capital structure, and financial performance on the stock prices of financial sector firms listed on the Indonesia Stock Exchange from 2020 to 2024. The used research methodology is a quantitative approach using multiple linear regression analysis tools. The study's findings indicate that the three independent factors significantly influence stock prices, both individually and together. The Adjusted R² value of 0.256 indicates that the three variables account for 25.6% of the variations in stock prices, whereas the remaining variance is affected by external factors not examined in this research. These results provide theoretical and practical advantages, particularly for investors in decision-making, for enterprises in financial management and governance, and for future researchers as a foundation for further research endeavours.